Effect of Threonine Supplementation on Broiler Chicken Productivity Traits - Al-Hayani , Waleed Khalid A. (International Journal of Poultry Science, 2017)
Objective: This study aimed to examine the impact of different amounts of threonine supplementation (0, 300, 600 and 900 mg kg–1) on physiological and productivity traits of broiler chickens. Materials and Methods: A total of 300 one day-old unsexed Ross 308 broilers were raised to the age for market (35 days). At the end of the experimental period, the Body Weight (BW), Weight Gain (WG), Feed Intake (FI) and feed conversion ratio (FC) were calculated. The Carcass Weight (CW), Dressing Percentage (DP), relative breast weight (BRp), percentage of carcass parts and internal organs were also assessed. Physiological and chemical blood tests were conducted on a sample of 12 birds per treatment (6 males, 6 females) at 21 and 35 days of age. Results: Significant improvement was observed in BW, WG, DP and BRp of birds fed diet supplemented with 900 mg kg–1 threonine compared to those of fed diet without threonine supplementation. This concentration of threonine also significantly increased of red blood count cells (RBC) as well as hematocrit (PCV%), calcium (Ca), phosphorus (P), alkaline phosphatase (ALP) and Growth Hormone (GH) levels, with a significant decrease in the H/L ratio. Conclusion: Supplementation of broiler chicken diets with 900 mg kg–1 threonine improved productivity traits.